Intellectual pollution and its relationship to life orientation among students of the Department of Special Education (Journal of the College of Basic Education, 2022)
The research aimed to find out: 1- Intellectual pollution among students of the Department of Special Education.2- The differences in intellectual pollution among students of the Department of Special Education according to the gender variable (males - females)3- Orientation towards life among students of the Department of Special Education.4- Differences in the orientation towards life among students of the Department of Special Education according to the gender variable (males - females)5- The relationship between intellectual pollution and life orientation among students of the Department of Special Education. The current research is limited to the students of the Department of Special Education in the College of Basic Education / Al-Mustansiriya University, of both sexes, and for the academic year (2020-2021), who number (200) male and female students. (28) Paragraph, and the researcher extracted the psychometric characteristics of the scales from validity, reliability and discrimination, and after using the appropriate statistical methods, the results showed the following: 1- There is intellectual pollution among the students of the Special Education Department.2- There are significant differences on the intellectual pollution scale in favor of male students of the Department of Special Education.3- Students of the Special Education Department have a negative attitude towards life.4- There are no differences in the orientation towards life according to the gender variable.5- There is a very weak relationship between intellectual pollution and life orientation among students of the Special Education Department. At the conclusion of the research, the researcher presented a number of recommendations and future proposals.